Hubungan Antara Pola Asuh Orang Tua Dengan Hasil Belajar Siswa Di SMP Swastyastu Tolai - Astija, Astija; Sandra, Tresia Virna (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2020)
Parenting patterns have an influence on learning outcomes. However, how much the influence and relationship level between the parenting of the parents with the student learning outcomes in Tolasty Swastyastu Middle School have not been studied. Therefore, the goals of the study is to determine the level of relationship between parenting parents with student learning outcomes and to determine the influence of parenting parents on student learning outcomes in Tolasty Swastyastu SMP. The study used a correlation method that connects the independent variable (X), parenting pattern, and dependent variable (Y), learning outcomes. The study collected 91 students from class VII A and B and class VIII A and B. Instrument of the study used a closed questionnaire consisting of 20 questions for parenting variables. An average value of even semester report was used for the student learning outcomes variable. Data was analysed with product moment correlation index. Result of the study obtained rxy = 0.825, indicating that the level of relationship between variables X (Parenting Parents) and Y (Student Learning Outcomes) is very strong. Moreover, the correlation was positively linier. Thus, it can be conluded that parenting patterns affect student learning outcomes (=68.1%).